2017
DOI: 10.1093/ejcts/ezx100
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival and quality of life after extracorporeal life support: a 10-year report†

Abstract: Long-term survival rates in patients requiring extracorporeal life support are acceptable with a probable advantage for patients without an operation and a narrowed QOL. The results are promising and encouraging, but there is also a need for improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
5
19
3
Order By: Relevance
“…3,7,23,24,26,27 Our registered levels of psychological distress are low compared with those of several other studies using the HADS. 9 Our 50% returnto-work rate is higher than that found by Hodgson et al 28 and Camboni et al 26 but lower than that reported by Tramm et al, 3 where two-thirds of the sample had returned to work by 1 year after ECMO treatment. 3 Somewhat at odds with this finding, Risnes et al found high rates of psychiatric morbidity several years after ECMO treatment, even in the survivors with no history of psychiatric disorder prior to ECMO treatment.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…3,7,23,24,26,27 Our registered levels of psychological distress are low compared with those of several other studies using the HADS. 9 Our 50% returnto-work rate is higher than that found by Hodgson et al 28 and Camboni et al 26 but lower than that reported by Tramm et al, 3 where two-thirds of the sample had returned to work by 1 year after ECMO treatment. 3 Somewhat at odds with this finding, Risnes et al found high rates of psychiatric morbidity several years after ECMO treatment, even in the survivors with no history of psychiatric disorder prior to ECMO treatment.…”
Section: Discussioncontrasting
confidence: 70%
“…2,4,5,[23][24][25] High rates of return to independence in self-care and daily activities, as found in the present study, have also been reported previously in other studies using the EQ-5D descriptive system. 3,7,23,24,26,27 Our registered levels of psychological distress are low compared with those of several other studies using the HADS. 2,3,5,9,10 In a prospective longitudinal study, Tramm et al found that mental health improved during the first year after ECMO and that psychological distress was higher in survivors who received psychological care prior to ECMO treatment.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The concomitant use of an intraaortic balloon pump (IABP) with ECMO as the easiest method to decompress the left ventricle is not part of our protocol, neither is the use of an Impella device. The overall survival rate to discharge of our entire cohort including nearly 50% of ECPR cases is 37% in accordance with the Extracorporeal Life Support Organization (ELSO) registry and similar to the published VA ECMO literature (16). The low rate of LV venting in our population is explained by our policy of strict afterload reduction, accepting a mean arterial pressure of <50 mmHg even with no pulsatility for a period of 24 h and sometimes even longer, low flow rates of 3-4 L/min as long as lactate levels decrease, a restrictive fluid management, as well as the application of higher positive end expiratory pressure values to decrease pulmonary edema.…”
supporting
confidence: 86%
“…It is seen that 75% of the survivors after ECLS are able to go about their daily life, 25% of them return to work or school, and 57% of them are not limited in their usual activities. However, when compared to a normative age-matched population, significantly lower quality-of-life indices are reported [76].…”
Section: Va-ecmomentioning
confidence: 76%